Universal Health Coverage and a pledge to empowering persons with disabilities and ensuring inclusiveness and equality; how does this year’s theme benefit the deaf/dumb - Juliet Mwale Musabula (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
No Abstract